TEACHING VOCABULARY USING VISUAL NARRATIVE - Kurniawati, Kurniawati; Regina, Regina; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to know the effectiveness of using Visual Narrative in increase the students’ vocabulary achievement to the eight grade student of MTsN 1 Pontianak in academic year 2014/2015. The problem of this research was design to investigate the effectiveness of the use Visual Narrative towards students’ vocabulary achievement. This research applied pre-experimental method. The research used one group of pre-test and post-test designed. The sample was 40 students of eight grade students of MTs Negeri 1 Pontianak. The technique to collect the data was measurement technique. The form of test was multiple choice and matching words, consist of 30 items of verbs and nouns about the story in the comic. The result of the research shows a good result that shown by the mean score of the students that increased from 63.32 (average to good) to 80.57 (good to excellent). Further, the result of t-test calculation is 10.29 which is bigger than t-table. Finally, based on the computation of the t-test and effect size, the Alternative Hypothesis is accepted and the Null Hypothesis is rejected. In conclusion, the use of Visual Narrative is effective to increase students’ vocabulary to the eighth grade students of MTs Negeri 1 Pontianak in Academic Year 2014/2015. Key words : Vocabulary, Visual Narrative, Comic